2021
DOI: 10.3390/plants10122786
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation with Ericoid Mycorrhizal Associations Alleviates Drought Stress in Lowland and Upland Velvetleaf Blueberry (Vaccinium myrtilloides) Seedlings

Abstract: Although velvetleaf blueberry (Vaccinium myrtilloides) is usually associated with sandy (upland) areas of the North American boreal forest, lowland populations can be also found in bogs, suggesting possible adaptations to different site conditions. In this study, we examined the role of ericoid mycorrhizal (ERM) fungi in conferring drought resistance to the upland and lowland velvetleaf blueberry seedlings. The seedlings were inoculated with four ERM fungi (Pezicula ericae, Pezoloma ericae, Meliniomyces variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…Mycorrhizas are well known to influence the physiological capacity of plants to tolerate drought, with many studies documenting direct and indirect mechanisms, such as mycelial transport of water and nutrients, leading to beneficial effects on plant performance, including improved survival under drought (Augé, 2001; Lehto & Zwiazek, 2011; Sebastiana et al ., 2018; Mu et al ., 2021; Püschel et al ., 2021). This would indicate that mycorrhizas might accelerate the evolutionary gains of drought tolerance by enhancing the transgenerational success of mycorrhizal plants that survive repeated droughts, compared with that of the less successful non-mycorrhizal counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mycorrhizas are well known to influence the physiological capacity of plants to tolerate drought, with many studies documenting direct and indirect mechanisms, such as mycelial transport of water and nutrients, leading to beneficial effects on plant performance, including improved survival under drought (Augé, 2001; Lehto & Zwiazek, 2011; Sebastiana et al ., 2018; Mu et al ., 2021; Püschel et al ., 2021). This would indicate that mycorrhizas might accelerate the evolutionary gains of drought tolerance by enhancing the transgenerational success of mycorrhizal plants that survive repeated droughts, compared with that of the less successful non-mycorrhizal counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the ecto-, ericoid, and arbuscular mycorrhizas have in common the ability to influence the physiological capacity of their host plants to tolerate drought, while drought can also influence the development of these mycorrhizas (Augé, 2001;Lehto & Zwiazek, 2011;Sebastiana et al, 2018;Kilpeläinen et al, 2020;Mu et al, 2021;Püschel et al, 2021). A major gap of knowledge is still how plant adaptation to drought and mycorrhizas influence one another at an evolutionary time scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, heat stress significantly reduced the availability of soil nutrient elements, leading to a reduction in plant biomass (Yeasmin et al, 2019). Mu et al (2021) reported that inoculation of ericoid mycorrhizae fungi can improve the heat and drought tolerance of plants and alleviate the damage of Rhododendron caused by heat stress. Therefore, plant growth and development under heat stress are closely related to soil nutrients, soil enzyme activities and other soil physicochemical properties, and soil microorganisms may also play an important role in the process of plant response to heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…The fungi associated with lingonberry are called Ericoid mycorrhizal (ErM) fungi ( Lukesova et al, 2015 ). ErM fungi are beneficial microorganisms for the growth of lingonberry, which can promote the growth and nutrient absorption of blueberry and reduce the damage to plants under drought, heavy metals, and saline-alkali environments ( Baba et al, 2021 ; Cai et al, 2021 ; Mu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%